A method for catalytically synthesizing polyethylene polyamines
Patent Information
- Application Number
- CN202610885678.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本发明解决了传统二氯乙烷法合成多乙烯多胺过程中催化剂稳定性差、金属易流失以及环状胺副产物含量高的问题
1、通过采用固态三聚氰胺经热缩聚与热氧化剥离制备 g-C3N4纳米片,经氮等离子体处理制造缺陷后,与硝酸镍/硝酸锌溶液进行界面还原及固相热处理,获得了Ni1Zn1/v-C3N4催化剂,提高了二氯乙烷的转化率以及长链线性多胺目标产物的选择性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalytic synthesis technology of polyethylene polyamines, specifically a method for catalytic synthesis of polyethylene polyamines. Background Technology
[0002] Polyethylene polyamines are important fine chemical intermediates, widely used in papermaking additives, chelating agents, and high-performance curing agents. Currently, the main industrial production method is the dichloroethane process. The traditional dichloroethane process is typically carried out under high pressure in the liquid phase, but it faces the challenge of controlling the thermodynamic probability of the reaction. During the conversion process, the raw material dichloroethane is prone to uncontrolled intramolecular cyclization, resulting in high levels of cyclic amine byproducts such as piperazines in the product, severely limiting the selectivity and product quality of high-boiling-point linear long-chain polyamines.
[0003] To improve reaction conversion and suppress byproducts, existing technologies often introduce transition metal catalysts. However, polyethylene polyamines, as strong complexing chelating ligands, readily exhibit strong directional chelation towards the active metal centers on the catalyst surface during the reaction. This leads to severe loss of the active metal component, and the catalyst structure is prone to coarsening or deactivation during long-term industrial operation, resulting in poor stability. Furthermore, the high resistance to dechlorination of the carbon-chlorine bond in dichloroethane during traditional reactions makes it difficult to simultaneously achieve high overall conversion and long-chain linear selectivity during continuous operation. Therefore, developing a highly stable catalytic synthesis method that effectively suppresses metal loss and significantly reduces the content of cyclic amine byproducts is a critical technical bottleneck that urgently needs to be addressed in the current dichloroethane method for preparing high-boiling-point polyamines. To this end, a method for the catalytic synthesis of polyethylene polyamines is proposed. Summary of the Invention
[0004] This invention solves the problems of poor catalyst stability, easy metal loss, and high content of cyclic amine byproducts in the traditional dichloroethane method for synthesizing polyethylene polyamines. By catalytically preparing polyethylene polyamines, it improves dichloroethane conversion and selectivity for long-chain linear polyamines, reduces the total content of cyclic amine byproducts, and inhibits metal loss.
[0005] To achieve the above objectives, the present invention provides the following method for the catalytic synthesis of polyethylene polyamines: The main steps include: Step 1: The prepared supported defect lattice confined catalyst powder, silica sol binder, and polyvinyl alcohol rheology modifier are mixed in deionized water at a mass ratio of 100:15:3. The mixture is sheared and stirred to prepare a coating slurry with a solid content of 20 wt%. The slurry is uniformly coated onto the inner wall of the microchannels of an integrated multi-channel microreactor using a vacuum impregnation method. It is dried at 100°C for 2 hours, then calcined and cured at 400°C for 3 hours under a nitrogen atmosphere to form a stable catalytic film. A pressure-resistant microchannel reaction system is assembled. Before introducing the material, an ammonia solution containing potassium hydroxide is continuously pumped countercurrently into the microchannels for in-situ liquid-phase pre-activation treatment. The polyvinyl alcohol in the raw material is essentially carbonized and decomposed after calcination at 400°C with N2 to form micropores. The final catalytic film consists of a Ni1Zn1 / v-C3N4 and SiO2 network.
[0006] Step 2: Thoroughly mix the refined dichloroethane and ammonia water materials according to the molar ratio, continuously press them into the fluid physical polarization cavity, turn on the ultrasonic transducer on the outside of the cavity to perform dual-frequency resonance, and at the same time turn on the continuous microwave generator to perform fluid physical polarization stretching control to obtain polarized material fluid.
[0007] Step 3: The polarized material fluid is continuously and tangentially injected into a microchannel reactor filled with a pre-activated catalyst bed to carry out a microchannel catalytic amination reaction, and a microchannel amination effluent is obtained.
[0008] Step 4: The microchannel amination effluent is directly introduced into the catalyst-free high-temperature hollow tube thermal condensation section for continuous thermal coupling segment polymerization. After the reaction is completed, 2-3 times the amount of anhydrous ethanol is continuously pumped into the effluent as a dilution and desalting solvent for the high-salt system. The temperature is lowered to 15℃-25℃ to allow the ammonium chloride and potassium chloride crystals produced by the reaction to fully precipitate. The solid salt particles are removed by continuous centrifugation using a continuous flow industrial centrifuge. The resulting clear liquid phase is continuously introduced into the dilution and desalting system to remove excess ammonia and anhydrous ethanol solvent. Finally, it is sent to a vacuum fractionation system for distillation to obtain the high-boiling-point polyamine product.
[0009] The fluid physical polarization cavity in step 2 is composed of a quartz / stainless steel double-wall structure. The ultrasonic transducer is attached to the bottom of the outer metal wall, and the microwave feed port is introduced through the quartz window on the side wall of the cavity.
[0010] Preferably, in step 1, the supported defect lattice confined catalyst is labeled as Ni1Zn1 / v-C3N4, where v represents a nitrogen vacancy defect; its preparation method is as follows: the heating rate of solid melamine in air atmosphere is adjusted to 2℃ / min-10℃ / min, for example, it can be 2℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, etc., heated to 500℃-600℃, continuously calcined for 3h-6h to carry out thermal polycondensation reaction, cooled and ground to a median particle size D50 of 5μm-15μm to obtain graphitic nitrogen carbide intermediate powder; Graphite phase nitrogen carbide intermediate powder was placed in air and subjected to thermal oxidation exfoliation treatment at 500℃-540℃ for 2h-5h to obtain g-C3N4 nanosheets with a layer thickness of 1.2nm-1.5nm. g-C3N4 nanosheets were fed into the cavity of an inductively coupled plasma device, pure nitrogen gas was introduced, the working pressure of the cavity was controlled at 30Pa-50Pa, and the working power was set at 200W-400W to perform nitrogen plasma directional bombardment treatment for 5min-35min, thus obtaining defect-state modified nitrogen carbide support.
[0011] Preferably, in step 1, the process of supporting the metal in the supported defect lattice confined catalyst is as follows: a mixed metal salt aqueous solution is prepared with the atomic molar ratio of nickel to zinc controlled at 1:1; the defect-modified nitrogen carbide support is uniformly dispersed in anhydrous ethanol using a shear emulsifier, with the dispersion speed controlled at 800 r / min-1500 r / min and the material temperature maintained at -5℃-5℃; the mixed metal salt aqueous solution is slowly added dropwise at a rate of 0.2 mL / min-0.6 mL / min under a mechanical stirring speed of 1000 r / min-1500 r / min; after the addition is completed, the coordination reaction is continued under light-protected conditions for 2 h-14 h.
[0012] The mixed metal salt aqueous solution is prepared by dissolving nickel nitrate and zinc nitrate in pure water. The total loading of active metals in the final catalyst (based on metal elements) accounts for 2.0%-8.5% of the total mass of the catalyst, preferably 4.0%-6.5%.
[0013] In this invention, by limiting the pressure, power, and time window of inductively coupled nitrogen plasma bombardment, high-density, uniformly confined nitrogen vacancy defects can be directionally manufactured in its unique nitrogen carbide lattice. In the subsequent low-temperature temperature field and light-shielded coordination crosslinking process, nickel and zinc ions in equimolar ratio can be captured and anchored in situ. The defect lattice confinement here can effectively change the local electronic coordination environment of metal ions, blocking the local thermal accumulation and lattice coarsening of transition metals at the atomic scale.
[0014] Preferably, in step 1, the interfacial coordination partial reduction induction and solid-phase heat treatment specifically involves: after the coordination reaction is completed, adding 3% sodium hydroxide solution to the system to adjust the pH value to 11-12, adding a hydrazine hydrate ethanol solution with a concentration of 10 mmol / L-20 mmol / L to the system, and controlling the material temperature in an ice-water bath environment of -5℃ to 5℃ for interfacial coordination and partial reduction induction for 2h-4h; after the reaction is completed, performing vacuum centrifugation washing 3-6 times, transferring it to a vacuum freeze-drying oven at -60℃ to -50℃ for drying for 24h-36h, and finally placing the solid product in a tube furnace and heating it to 300℃-600℃ for solid-phase heat treatment for 4h-6h under the protection of high-purity nitrogen at a flow rate of 100mL / min-200mL / min, and obtaining a supported defect lattice confined catalyst after cooling.
[0015] Preferably, in step 1, the catalyst coating and in-situ pre-activation specifically involve: controlling the thickness of the catalytic membrane coated inside the integrated multi-channel microreactor to be 50μm-100μm, for example, 50μm, 65μm, 80μm, 100μm, etc.; and using an ammonia solution containing potassium hydroxide for in-situ pre-activation in the liquid phase, wherein the mass fraction of ammonia is 25%-30% and the mass fraction of potassium hydroxide is 3%-5%. The specific process parameters for continuous pre-activation are as follows: the activation temperature is controlled at 85℃-95℃, the activation pressure is 1.2MPa-2.0MPa, and the liquid hourly space velocity is 3.0h. -1 -6.0h -1 Continuous cyclic immersion and rinsing activation treatment for 2.0h-4.0h.
[0016] Preferably, in step 2, the specific process parameters for the external field fluid physical polarization of the material are as follows: the initial molar ratio of the mixed material between refined dichloroethane and ammonia water with a mass fraction of 25%-30% is controlled at 1:12-1:18, for example, it can be 1:12, 1:15, 1:16, 1:18, etc.; the Reynolds number of the material fluid in the fluid physical polarization cavity is controlled at 2100-2800, which is in the transition turbulent region to achieve efficient external field polarization and interphase mixing; the ultrasonic transducer adopts a dual-frequency resonance mode with a combined frequency of 60kHz and 100kHz, and the total ultrasonic power is controlled at 400W-600W; the working frequency of the continuous microwave generator is locked at 2450MHz, and the constant working power is controlled at 700W-900W; the flow rate of the material fluid in the fluid physical polarization cavity is regulated to a total residence time of 8s-15s.
[0017] In this invention, a cascaded fluid physical polarization field is placed before the multi-channel microreactor to induce transient physical polarization between highly polar ammonia molecules and dichloroethane fluid under the superimposed synergistic effect of a dual-frequency ultrasonic resonance field and a high-power microwave field. By utilizing alternating electromagnetic control and ultrasound, the C-Cl bonds within the dichloroethane molecules are pre-activated before entering the catalytic reaction bed, increasing the kinetic rate of intramolecular C-Cl bond cleavage and inhibiting the formation of cyclic amine byproducts such as piperazine.
[0018] Preferably, in steps 3 and 4, the specific process parameters for the continuous operation of continuous flow catalytic amination and subsequent thermal condensation are as follows: the polarized material fluid is tangentially injected into the microchannel of the microchannel reactor from the polarization chamber. Due to the reduction in the equivalent diameter of the channel, the fluid becomes a strictly laminar flow state inside the microchannel, and its liquid hourly space velocity is controlled at 15 h⁻¹. -1 -25h -1 The working reaction temperature inside the microchannel reactor is controlled at 125℃-140℃, and the working pressure is controlled at 2.8MPa-3.5MPa. After the reaction fluid flows out of the microchannel, it directly enters the catalyst-free high-temperature hollow tube thermal condensation section. The reaction temperature of the thermal condensation section is controlled to be stably maintained at 175℃-195℃, and the running residence time is controlled at 10min-15min. After dilution with anhydrous ethanol pumped into the system, salt filtration by continuous centrifuge, and solvent removal by flash evaporation, the effluent is finally obtained by vacuum distillation at above 200℃ and under a pressure of 10mmHg through a cascade fractionation system to obtain the high-boiling-point polyamine product.
[0019] Furthermore, the high-boiling-point polyamine products are a mixed linear chain of pentaethylenehexamine, hexaethyleneheptaamine, heptaethyleneoctaamine, octaethylenenonamine, and nonaethylenedecaamine. The total nitrogen content of the products obtained by distillation is stably maintained at 30.2%-33.4%, and the target distillation volume ratio above 200℃ reaches 42%-67%. Moreover, the final specific gravity of the products is controlled within the range of 1.005-1.038 (measurement temperature conditions are 20℃ relative to 4℃ water).
[0020] Furthermore, in the continuous flow microchannel catalytic application system, when the continuous operation reaction time is ≥50h, due to the unique single-point coordination structure of the catalyst, the directional chelation loss of strongly complexed polyamine products to the active center is blocked, so that the cumulative total loss rate of active metals nickel and zinc in the discharged material is controlled at the level of 0.04ppm / 50h-0.28ppm / 50h.
[0021] Preferably, the pure solid melamine used has a purity ≥99.5%, ash content ≤0.03%, and CAS number 108-78-1; pure nickel nitrate (nickel nitrate hexahydrate) has a purity ≥99.0%; pure zinc nitrate (zinc nitrate hexahydrate) has a purity ≥99.0%; electronic grade hydrazine hydrate solution has a mass concentration of 80% (aqueous solution basis), and CAS number 10217-52-4; industrial grade refined 1,2-dichloroethane has a purity ≥99.8%, moisture content ≤100ppm, and CAS number 107-06-2; and industrial grade pure potassium hydroxide has a purity ≥95.0%.
[0022] This invention also provides a high-boiling-point polyamine product prepared by any of the above-mentioned process routes. Because the intramolecular cyclization side reaction pathway is interrupted in situ and the continuous free thermal coupling growth path of residual lower amines is opened, the total mass percentage of cyclic amine byproducts such as 1,4-diazacyclohexane (piperazine), 2-(piperazin-1-yl)ethyl-1-amine, and 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine) in the resulting product is significantly reduced and maintained within the range of 1.4%-5.8%. This achieves a directional shift of the product distribution towards the long-chain, high-boiling-point linear polyamine range, with a total dichloroethane reaction conversion rate as high as 78.4%-95.1% and a high-boiling-point polyamine product selectivity of 54.1%-71.3%. In this invention, both the dichloroethane conversion rate (%) and the high-boiling-point polyamine product selectivity (%) are calculated based on the carbon atom conservation (carbon balance) during the reaction process. The selectivity of high-boiling-point polyamine products refers to the percentage of moles of dichloroethane consumed in the formation of linear long-chain polyamines out of the total moles of dichloroethane consumed. The formula for calculating selectivity is as follows: M represents the target polyamine, i is the molar yield of the i-th target linear polyamine (pentaethylenehexamine i=5, hexaethyleneheptaethyleneamine i=6, heptaethyleneoctaethyleneamine i=7, octaethylenenonamine i=8, nonaethylenedecaethyleneamine i=9); n represents the number of dichloroethane conversion structural units contained in the target polyamine molecule, i.e., the corresponding number of two-carbon segments, pentaethylenehexamine n=5, and so on; the 2 in the denominator indicates that each molecule of dichloroethane provides 2 carbon atoms.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. g-C3N4 nanosheets were prepared by thermal polycondensation and thermal oxidative exfoliation of solid melamine. After creating defects by nitrogen plasma treatment, Ni1Zn1 / v-C3N4 catalyst was obtained by interfacial reduction and solid-state heat treatment with nickel nitrate / zinc nitrate solution. This improved the conversion rate of dichloroethane and the selectivity of the target product of long-chain linear polyamine.
[0024] 2. After coating the catalyst onto the integrated multi-channel microreactor, an ammonia solution containing potassium hydroxide is first pumped in countercurrently before the material is introduced for in-situ liquid-phase pre-activation. In subsequent processes, the purified dichloroethane and ammonia material are passed through a fluid physical polarization chamber. Combined with the catalyst-free high-temperature hollow tube thermal condensation section set in the later stage of the microchannel reaction, the product distribution is regulated, and the unreacted residual dichloroethane undergoes thermal coupling segment polymerization, reducing the total content of cyclic amine byproducts such as 1,4-diazacyclohexane, 2-(piperazin-1-yl)ethyl-1-amine, and 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine).
[0025] 3. The catalyst exhibits good resistance to metal loss and stability during long-term industrial operation in microchannel tests. Under continuous flow system, the active metal loss rate is low after 50 hours of continuous reaction. The total nitrogen content of the high-boiling polyamine target product obtained by distillation is maintained stably. Furthermore, the target distillate volume ratio is increased at temperatures above 200℃ and pressures of 10 mmHg, and the final specific gravity of the product is increased. Attached Figure Description
[0026] Figure 1 This is a comparison chart of the dichloroethane conversion rate, high-boiling-point polyamine product selectivity, and active metal loss rate between Example 1 of the present invention and various comparative examples. Figure 2 This is a comparison chart of the test results of the present invention under different process window application groups A, B, and C. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Please refer to... Figures 1 to 2 This invention provides a method for the catalytic synthesis of polyethylene polyamines, the technical solution of which is as follows: Example
[0028] 30.000±0.001g of solid melamine was placed in a covered high-alumina crucible and transferred to a muffle furnace. The crucible was heated to 550℃ in air at a heating rate of 5℃ / min and continuously calcined at this temperature for 4 hours to induce a thermal polycondensation reaction, yielding yellow, blocky graphitic nitrogen carbide. After cooling to room temperature, the powder was ground using an air jet mill and sieved. 10.000±0.001g of intermediate powder with a median particle size D50 of 8.5μm was placed in an open quartz boat and transferred back into a tube furnace. The furnace was then subjected to thermal oxidation and exfoliation treatment at 520℃ in air for 3 hours to obtain g-C3N4 nanosheets with a layer thickness of 1.2 to 1.5nm.
[0029] 7.800g of the nanosheet solid powder obtained by the above exfoliation was sent into the cavity of an inductively coupled plasma device, pure nitrogen gas was introduced, the working pressure of the cavity was 40Pa, and nitrogen plasma with a power of 300W was used for directional bombardment for 18min to obtain a modified carrier for later use.
[0030] Prepare 60 mL of an aqueous solution containing 0.520 g nickel nitrate and 0.531 g zinc nitrate, with the atomic molar ratio of nickel to zinc controlled at 1:1; uniformly disperse 7.800 ± 0.001 g of the modified carrier prepared in the first step in 300 mL of anhydrous ethanol using a shear emulsifier, and place the mixture in a 0 °C ice-water bath.
[0031] With stirring at 1200 r / min, 60 mL of mixed metal salt aqueous solution was added dropwise to the carrier dispersion at a rate of 0.4 mL / min. After the addition was completed, stirring was continued at 0℃ in the dark for 8 h.
[0032] After stirring, a 10wt% sodium hydroxide solution was slowly added dropwise to the system to adjust the pH to 11.5. Then, 40 mL of a 15 mmol / L hydrazine hydrate ethanol solution was added at a rate of 2 mL / min. The reaction was carried out in an ice-water bath for 3 hours. The resulting solid product was washed five times by vacuum centrifugation with anhydrous ethanol, and then dried in a vacuum freeze-drying oven at -55℃ for 30 hours. The dried solid product was then placed in a quartz tube furnace and subjected to solid-phase heat treatment at 450℃ for 5 hours under high-purity nitrogen at a flow rate of 150 mL / min. The resulting catalyst, labeled Ni1Zn1 / v-C3N4, was obtained after the heat treatment.
[0033] Examples 2-7: The preparation method of the catalyst is the same as in Example 1, with the following parameters adjusted.
[0034]
[0035] Comparative Example 1 In the first step of carrier treatment, after the g-C3N4 nanosheets are prepared, no nitrogen plasma is introduced to create defects. Instead, the unmodified nanosheet solid powder is directly used for the second step of metal salt drop-addition coordination. Other preparation methods are consistent with those in Example 1.
[0036] Comparative Example 2 In the second step of coordination curing, the active metal composition was changed, and an aqueous solution containing 1.040 g of nickel nitrate and no zinc nitrate was prepared in 60 mL. The total molar amount of metal in the reaction was kept consistent with that in Example 1, so that only a single active site of nickel metal existed on the catalyst surface. Other preparation methods were no different from those in Example 1.
[0037] Comparative Example 3 Compared with the method in Example 1, in the fourth step of the process application section, before the mixed fluid enters the microchannel reactor, the ultrasonic transducer and the focused microwave generator outside the fluid physical polarization cavity are turned off, that is, the material fluid only passes through the polarization cavity statically.
[0038] Comparative Example 4 Compared to the method in Example 1, in the fourth step of the process application section, after the material fluid flows out of the microchannel reactor, it is directly cooled and introduced into the dilution, desalination and fractionation system without passing through any catalyst-free high-temperature hollow tube thermal condensation section.
[0039] A method for catalytic synthesis of polyethylenepolyamines specifically involves preparing a slurry with a solid content of 20 wt% by mixing the catalyst powder prepared in Example 1 with silica sol and polyvinyl alcohol (PVA1788) at a mass ratio of 100:15:3. This slurry is then uniformly coated onto the inner wall of the microchannels of an integrated multi-channel microreactor using a vacuum impregnation method. After drying at 100°C and curing under nitrogen at 400°C, the catalytic film thickness is controlled to be 80 μm. A pressure-resistant microchannel reaction system is then assembled. Before introducing the material, in-situ liquid-phase pre-activation is performed at the catalyst interface by continuously countercurrently pumping 28% ammonia solution into the microchannels, mixed with 4% potassium hydroxide. The activation temperature is controlled at 90°C, the activation pressure at 1.5 MPa, and the liquid hourly space velocity at 4.5 h⁻¹. -1 The material was continuously circulated and activated for 3.0 hours. Refined dichloroethane and 28% ammonia water were thoroughly mixed at a molar ratio of 1:15 and continuously injected into the fluid physical polarization chamber. The Reynolds number within the polarization chamber was controlled at 2500. The ultrasonic transducer on the outside of the chamber was activated, employing a dual-frequency resonance of 60kHz and 100kHz with a total power of 500W. Simultaneously, a continuous microwave generator was activated at a working frequency of 2450MHz with a constant power of 800W. The flow rate of the material fluid within the polarization chamber was controlled to maintain a residence time of 10s.
[0040] The activated material fluid has a volume hourly space velocity of 20 h⁻¹. -1The reaction fluid is tangentially injected into a microchannel reactor filled with catalyst. The working reaction temperature inside the microchannel reactor is 130℃, and the working pressure is 3.2MPa. After exiting the microchannel reactor, the reaction fluid is directly introduced into a high-temperature empty tube thermal condensation section without catalyst. The reaction temperature of this thermal condensation section is adjusted to 185℃, and the residence time is 12min, so that the unreacted residual dichloroethane undergoes thermal coupling segment polymerization in the high-temperature zone. The product distribution is adjusted to shift towards the mixed polyamine range of pentaethylenehexamine to nonaethylenedecaamine. After continuous reaction for 50h, 2.5 times the mass of anhydrous ethanol is continuously pumped into the reaction effluent. The precipitated inorganic salt solids are removed by static continuous flow centrifugation at 20℃. The resulting liquid phase is diluted, desalted, and desolventized, and finally sent to a vacuum fractionation system. The high-boiling polyamine target product was extracted at temperatures above 200°C and under a pressure of 10 mmHg. Its final specific gravity was measured to be 1.032. The measurement temperature conditions were 20°C relative to 4°C water. The total nitrogen content was 32.6%, and the distillation volume at temperatures above 200°C accounted for 63%.
[0041] The high-boiling polyamine target product obtained by the catalyst treatment in Example 2 had a final specific gravity of 1.018, a total nitrogen content of 31.5%, and a distillation volume percentage of 55% above 200°C.
[0042] The high-boiling polyamine target product obtained by the catalyst treatment in Example 3 had a final specific gravity of 1.025, a total nitrogen content of 33.1%, and a distillation volume ratio of 60% above 200°C.
[0043] The high-boiling polyamine target product obtained by the catalyst treatment in Example 4 had a final specific gravity of 1.021, a total nitrogen content of 32.2%, and a distillation volume percentage of 58% above 200°C.
[0044] The high-boiling polyamine target product obtained by the catalyst treatment in Example 5 had a final specific gravity of 1.029, a total nitrogen content of 32.8%, and a distillation volume percentage of 61% above 200°C.
[0045] The high-boiling polyamine target product obtained by the catalyst treatment in Example 6 had a final specific gravity of 1.005, a total nitrogen content of 30.2%, and a distillation volume percentage of 42% above 200°C.
[0046] The high-boiling polyamine target product obtained by the catalyst treatment in Example 7 had a final specific gravity of 1.036, a total nitrogen content of 33.4%, and a distillation volume percentage of 53% above 200°C.
[0047] The high-boiling polyamine target product obtained by catalyst treatment in Comparative Example 1 had a final specific gravity of 0.992, a total nitrogen content of 28.4%, and a distillation volume percentage of 26% above 200℃.
[0048] The high-boiling polyamine target product obtained by catalyst treatment in Comparative Example 2 had a final specific gravity of 1.011, a total nitrogen content of 31.0%, and a distillation volume percentage of 45% above 200℃.
[0049] The high-boiling polyamine target product obtained by catalyst treatment in Comparative Example 3 had a final specific gravity of 1.014, a total nitrogen content of 31.2%, and a distillation volume percentage of 48% above 200℃.
[0050] The high-boiling polyamine target product obtained by catalyst treatment in Comparative Example 4 had a final specific gravity of 0.996, a total nitrogen content of 32.5%, and a distillation volume percentage of 21% above 200℃.
[0051] The conversion rate of dichloroethane, the selectivity of high-boiling-point polyamine products, the total nitrogen content of high-boiling-point polyamines, the content of byproduct piperazine (PIP), the content of cyclic amines, and the deactivation rate and active metal loss rate of the catalyst during continuous operation were tested. Catalyst evaluation was conducted in the examples, comparative examples, and each catalytic activation application group. Qualitative and quantitative analysis of the products was performed using gas chromatography-mass spectrometry (GC-MS). Separation was performed using a Restek Rtx-51 Amine capillary column, and quantitative analysis of the eluent was performed using the external standard method. Some analytical results are listed in Table 2. In this scheme, the dichloroethane conversion rate of each group was uniformly calculated based on the dichloroethane consumption data, and the calculation formula is as follows: C 初始 C represents the initial mass concentration of dichloroethane in the mixture continuously injected into the fluid physical polarization chamber. 最终 The mass concentration of residual dichloroethane in the effluent sample during stable reaction operation.
[0052] The selectivity of the high-boiling-point polyamine products was the sum of the selectivities of pentaethylenehexamine, hexaethyleneheptaamine, heptaethyleneoctaamine, octaethylenenonamine, and nonaethylenedecaamine. The byproducts, piperazines and cyclic amines, were 1,4-diazacyclohexane, 2-(piperazin-1-yl)ethyl-1-amine, 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine), 2-(4-(2-aminoethyl)piperazin-1-yl)ethyl-1-amine, and 1,4-diazabicyclo[2.2.2]octane, respectively. The loading of active metal elements on the catalyst and the metal loss rate after the reaction were determined by inductively coupled plasma mass spectrometry.
[0053]
[0054] Specifically, such as Figure 1Table 2 shows the results of dichloroethane conversion, high-boiling-point polyamine product selectivity, and cumulative total loss rate of active metals after 50 hours of continuous operation for Examples 1 and the comparative examples of the present invention. Example 1 shows a balance in conversion, high-boiling-point polyamine selectivity, and anti-loss performance. The coordination saturation and geometry of the structure are optimal. The appropriate amount of nitrogen vacancies generated by plasma bombardment, under heat treatment at 450°C, makes the local electron densities of equimolar Ni and Zn complementary. The Lewis acid sites of Zn single atoms and the electron-rich centers of Ni single atoms synergistically initiate a nucleophilic-electrophilic dual-drive mechanism, reducing the activation energy of carbon-chlorine bonds. At the same time, the single-point coordination mode avoids multi-site chelation of long-chain polyamines and inhibits metal loss. As the Zn ratio increases and the defect density decreases in Examples 2, 4, and 6, the Ni active sites are insufficient, and the conversion rate decreases. In Examples 3, 5, and 7, the Ni ratio is too high or the heat treatment temperature is too high, which easily causes local thermal aggregation of some single atoms, causing the high-boiling-point polyamine selectivity to decrease to varying degrees due to the weakening of steric hindrance.
[0055] Comparative Example 1, lacking plasma treatment and lattice vacancy confinement, resulted in the metal agglomerating into conventional nanoparticles during reduction. The highly complexed polyamine products led to severe metal chelation loss, significantly increasing the deactivation rate. Comparative Example 2, lacking the electronic synergistic effect of heteronuclear dual active sites, experienced increased resistance to carbon-chlorine bond dechlorination, resulting in a significant deterioration in conversion and selectivity. Comparative Example 3, with the physical polarization field shut off, prevented the carbon-chlorine bonds from undergoing polarization stretching before the reaction, leading to an increase in cyclic amine byproducts. Comparative Example 4, lacking the free thermal condensation process of the high-temperature hollow tube segment, prevented the lower amine from continuing chain segment growth through thermal coupling, resulting in a severely low selectivity for the final high-boiling polyamine.
[0056] Based on the above tests, specific catalytic performance tests were conducted on the catalysts in Example 1 group. The specific group settings are shown below, and the test results are summarized in […]. Figure 2 middle.
[0057] Catalytic activation application group A The catalyst prepared in Example 1 was uniformly coated onto the inner wall of the microchannel of the integrated multichannel microreactor by vacuum impregnation, and the thickness of the catalytic film was controlled to be 80 μm. A pressure-resistant microchannel reaction system was then assembled.
[0058] Before introducing the material, the catalyst surface interface is pre-activated in situ in the liquid phase. Ammonia water with a mass fraction of 28% is continuously pumped into the microchannel in a countercurrent manner, and potassium hydroxide with a mass fraction of 4% is mixed in. The activation temperature is controlled at 95℃, the activation pressure is 1.2MPa, the liquid hourly space velocity is 6.0 / h, and the continuous circulation wetting and rinsing activation treatment is carried out for 2.0h to induce the formation of an alkaline adsorption environment at the catalyst bed surface interface.
[0059] Refined dichloroethane and ammonia water with a mass fraction of 28% were thoroughly mixed at a molar ratio of 1:12 and continuously injected into the fluid physical polarization chamber. The ultrasonic transducer on the outside of the chamber was activated, using a dual-frequency resonance of 60kHz and 100kHz with a total power of 600W. At the same time, a continuous microwave generator was activated with a working frequency of 2450MHz and a constant power of 900W. The flow rate of the material fluid in the polarization chamber was controlled to maintain a residence time of 8s.
[0060] The activated material fluid is tangentially injected into a microchannel reactor filled with catalyst at a Reynolds number of 2800. The working reaction temperature inside the microchannel reactor is 140℃ and the working pressure is 3.5MPa.
[0061] After exiting the microchannel reactor, the reaction fluid was directly introduced into a catalyst-free, high-temperature hollow tube thermal condensation section. The reaction temperature of this section was adjusted to 175°C, and the residence time was set to 15 min. This allowed unreacted residual dichloroethane to undergo thermal coupling segment polymerization in the high-temperature zone, adjusting the product distribution to shift towards a mixed polyamine range from pentaethylenehexamine to nonaethylenedecaamine. After continuous reaction for 50 h, the reaction effluent was diluted, desalted, and fractionated under reduced pressure. The high-boiling target polyamine product was then collected at temperatures above 200°C and under a pressure of 10 mmHg.
[0062] Catalytic activation application group B The catalyst prepared in Example 1 was uniformly coated onto the inner wall of the microchannel of the integrated multichannel microreactor by vacuum impregnation, and the thickness of the catalytic film was controlled to be 80 μm. A pressure-resistant microchannel reaction system was then assembled.
[0063] Before introducing the material, the catalyst surface interface is pre-activated in situ in the liquid phase. Ammonia water with a mass fraction of 28% is continuously pumped into the microchannel in a countercurrent manner, and potassium hydroxide with a mass fraction of 4% is mixed in. The activation temperature is controlled at 85℃, the activation pressure is 1.8MPa, the liquid hourly space velocity is 3.0 / h, and the continuous circulation wetting and rinsing activation treatment is carried out for 4.0h.
[0064] Refined dichloroethane and ammonia water with a mass fraction of 28% were thoroughly mixed at a molar ratio of 1:18 and continuously injected into the fluid physical polarization chamber. The ultrasonic transducer on the outside of the chamber was activated, using a dual-frequency resonance of 60kHz and 100kHz with a total power of 400W. At the same time, a continuous microwave generator was activated with a working frequency of 2450MHz and a constant power of 700W. The flow rate of the material fluid in the polarization chamber was controlled to maintain a residence time of 15s.
[0065] The activated material fluid is tangentially injected into a microchannel reactor filled with catalyst at a Reynolds number of 2100. The working reaction temperature inside the microchannel reactor is 125℃ and the working pressure is 2.8MPa.
[0066] After exiting the microchannel reactor, the reaction fluid was directly introduced into a catalyst-free, high-temperature, hollow-tube thermal condensation section. The reaction temperature of this section was adjusted to 195°C, and the residence time was set to 10 min. This allowed unreacted residual dichloroethane to undergo thermal coupling segment polymerization in the high-temperature zone, adjusting the product distribution to shift towards a mixed polyamine range from pentaethylenehexamine to nonaethylenedecaamine. After continuous reaction for 50 h, the reaction effluent was diluted, desalted, and fractionated under reduced pressure. The high-boiling target polyamine product was then collected at temperatures above 200°C and under a pressure of 10 mmHg.
[0067] Catalytic activation application group C The catalyst prepared in Example 1 was uniformly coated onto the inner wall of the microchannel of the integrated multichannel microreactor by vacuum impregnation, and the thickness of the catalytic film was controlled to be 80 μm. A pressure-resistant microchannel reaction system was then assembled.
[0068] Before introducing the material, the catalyst surface interface is pre-activated in situ in the liquid phase. Ammonia water with a mass fraction of 28% is continuously pumped into the microchannel in a countercurrent manner, and potassium hydroxide with a mass fraction of 4% is mixed in. The activation temperature is controlled at 92℃, the activation pressure is 2.0MPa, the liquid hourly space velocity is 4.0 / h, and the continuous circulation wetting and rinsing activation treatment is carried out for 3.5h.
[0069] Refined dichloroethane and ammonia water with a mass fraction of 28% were thoroughly mixed at a molar ratio of 1:16 and continuously injected into the fluid physical polarization chamber. The ultrasonic transducer on the outside of the chamber was activated, with a combined frequency of 60kHz and 100kHz for dual-frequency resonance and a total power of 450W. At the same time, a continuous microwave generator was activated with a working frequency of 2450MHz and a constant power of 850W. The flow rate of the material fluid in the polarization chamber was controlled to maintain a residence time of 11s.
[0070] The activated material fluid is tangentially injected into a microchannel reactor filled with catalyst at a Reynolds number of 2400. The working reaction temperature inside the microchannel reactor is 135℃ and the working pressure is 3.0MPa.
[0071] After exiting the microchannel reactor, the reaction fluid was directly introduced into a catalyst-free, high-temperature hollow tube thermal condensation section. The reaction temperature of this thermal condensation section was adjusted to 180℃, and the residence time was set to 13 min. This allowed unreacted residual dichloroethane to undergo thermal coupling segment polymerization in the high-temperature zone, adjusting the product distribution to shift towards a mixed polyamine range from pentaethylenehexamine to nonaethylenedecaamine. After 50 h of continuous reaction, the reaction effluent was diluted, desalted, and fractionated under reduced pressure. The high-boiling polyamine target product was collected at temperatures above 200℃ and under a pressure of 10 mmHg. The active metal loss rates for application groups A, B, and C were 0.08 ppm / 50 h, 0.04 ppm / 50 h, and 0.05 ppm / 50 h, respectively. The test results for dichloroethane conversion, high-boiling polyamine product selectivity, total nitrogen content of high-boiling polyamines, and the content of byproducts piperazine and cyclic amines are as follows: Figure 2 As shown, EDC is 1,2-dichloroethane. In application group A, the dechlorination of dichloroethane is activated, the catalytic amination reaction rate is amplified, and the conversion rate of dichloroethane reaches the highest value in the group. However, the selectivity of its long-chain linear polyamine is inhibited to some extent by high-temperature side reactions. When switching to application group B, as... Figure 2 The specificity assay showed that although the basic conversion rate slightly decreased to 89.2%, the directional selectivity of the high-boiling-point polyamine product reached the highest peak in the entire group. At the same time, the total content of byproducts piperazine and cyclic amines was effectively locked and reduced, and the loss rate of active metals decreased to 0.04 ppm / 50h. In contrast, application group C showed a steady-state intermediate value with balanced indicators. By controlling the pre-activated carbon-chlorine bonds through alternating electromagnetic regulation of the external field of the pre-fluid physical polarization chamber, and cascading the catalyst-free high-temperature empty tube section in the later stage, the residual amine underwent continuous free thermal coupling segment polymerization, thereby achieving good conversion and reducing the content of byproducts.
[0072] Through the above specific application performance tests, the high external field and high temperature amplify the carbon-chlorine bond activation energy and improve the basic conversion rate; while the high ammonia ratio, slow flow rate and long thermal condensation suppress cyclization side reactions, thereby increasing the selectivity of high-boiling-point polyamines and the target distillation ratio.
[0073] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.
Claims
1. A method for catalytic synthesis of polyethylene polyamines, using dichloroethane and ammonia as starting materials, characterized in that, This includes the catalytic synthesis of the polyethylene polyamine using a Ni1Zn1 / v-C3N4 catalyst.
2. The method for catalytic synthesis of polyethylene polyamines according to claim 1, characterized in that, The preparation method of the Ni1Zn1 / v-C3N4 catalyst is as follows: Melamine is heated to 500℃-600℃ in air to carry out a thermal polycondensation reaction. After being ground, it is placed in air and subjected to thermal oxidation exfoliation treatment at 500℃-540℃ to obtain an intermediate solid powder. The solid powder is fed into the cavity of an inductively coupled plasma device and subjected to nitrogen plasma bombardment treatment with pure nitrogen gas to obtain a support. The support is loaded with metal to obtain the Ni1Zn1 / v-C3N4 catalyst.
3. The method for catalytic synthesis of polyethylene polyamines according to claim 2, characterized in that, In the thermal polycondensation reaction, the heating rate is 2℃ / min-10℃ / min, and the calcination time is 3h-6h; the conditions for the nitrogen plasma bombardment treatment are a working pressure of 30Pa-50Pa, a working power of 200W-400W, and a treatment time of 5min-35min.
4. The method for catalytic synthesis of polyethylene polyamines according to claim 2 or 3, characterized in that, The specific method for loading the metal onto the carrier is as follows: a mixed metal salt aqueous solution is prepared with the atomic molar ratio of nickel to zinc controlled at 1:1; the carrier is dispersed in anhydrous ethanol, and the mixed metal salt aqueous solution is added dropwise at a rate of 0.2 mL / min to 0.6 mL / min at -5℃ to 5℃ with stirring, and stirred in the dark for 2h to 14h; after coordination, hydrazine hydrate ethanol solution is added dropwise to the system to carry out an interfacial reduction reaction for 2h to 4h; the solid product after the reaction is washed and then transferred to a vacuum freeze-drying oven for drying for 24h to 36h; the dried solid product is loaded into a tube furnace and heated to 300℃ to 600℃ under nitrogen protection for solid-phase heat treatment for 4h to 6h.
5. The method for catalytic synthesis of polyethylene polyamines according to claim 4, characterized in that, The mixed metal salt aqueous solution is prepared by dissolving nickel nitrate and zinc nitrate in pure water; the total active metal loading in the final catalyst accounts for 2.0%-8.5% of the total mass of the catalyst, calculated by metal element.
6. The method for catalytic synthesis of polyethylene polyamines according to claim 1, characterized in that, The method also includes coating the inner wall of a microchannel reactor with a mixture of the Ni1Zn1 / v-C3N4 catalyst and a binder, and continuously countercurrently pumping an ammonia solution containing potassium hydroxide into the microchannel for pre-activation treatment. The polyethylene polyamine is obtained through polarization reaction, amination reaction, thermal condensation, dilution and desalting, vacuum fractionation and rectification.